ANALYSIS OF THE EFFECTIVENESS OF THE COMPANY’S INNOVATION-DRIVEN GROWTH - Konovalenko, Sergey; Savvateev, Evgeniy; Udaltsova, Natalya (Revista Inclusiones, 2020)
The current methodological developments used to analyze the effectiveness of innovation-driven growth of economic agents in Russia do not ensure a comprehensive and objective systemic assessment of the effectiveness of the company’s innovation activities. The analytical tools used in practice do not allow to establish the reasons for the low growth rates of indicators that measure the effectiveness of financial and economic activities. This, in turn, does not allow to identify reserves for increasing labor productivity and to form an effective business strategy for an economic agent. Due to this, a need arises to formulate new methodological approaches used to analyze the effectiveness of innovation-driven growth of commercial companies.